Hydraulic Jump Characteristics Downstream of a Compound Weir consisting of Two Rectangles with a below Semicircular Gate - Alsaydalani, Majed (Engineering, Technology & Applied Science Research, 2024)
Weirs are often used in laboratories, industries, and irrigation channels to measure discharge. The discharge capacity of a structure is vital for its safety and plays an important role in the combined gate-weir flow, which is a complicated phenomenon in hydropower. This study carried out experiments on a combined hydraulic structure, which included a compound sharp-crested weir made up of two rectangles along with an inverted semicircular sharp gate. Installed on a straight channel, this structure served as a control instrument. The study aimed to investigate the downstream hydraulic jump characteristics of this combined structure, specifically, the sequent depth ratio (y2/y1), the hydraulic jump height ratio (Hj/y1), the energy loss ratio through the jump (EL/Eu), and the jump length ratio (Lj/y1). The width of the upper rectangle on the weir was set at 20 cm. The width of the lower rectangle (W2) was set at 5, 7, and 9 cm, while its depths (z) were fixed at 6, 9, and 11 cm. The gate’s diameters varied between 8, 12, and 15 cm. These measurements were alternated with varying initial Froude numbers (Fn1) ranging between 1.32 and 1.5. The results showed that the dimensions of both the weir and the gate influenced the hydraulic jump characteristics. Empirical formulas were developed to predict y2/y1, Hj/y1, EL/Eu, and Lj/y1 based on the differing dimensions of the combined structure. The findings and analysis of this study are limited to the range of data that were tested.